11. Study of the feasibility of a daily constancy check for VMAT using the Stealth® transmission chamber. (December 2017) - Nigoul, J.M.; Gempp, S.; Desrousseaux, J.; Capdeville, S.; Benkreira, M.
Abstract : Introduction: Volumetric Modulated Arc Therapy (VMAT) is a complex technique that requires additional controls over regulation. The aim of this study was to set up a fast and reliable daily constancy check of the VMAT to detect a problem in the beam delivery parameters. Methods: For this work, a Stealth® transmission chamber (IBA Dosimetry) was used, it is directly attached to the head of the linac, connected to a Dose1 (IBA Dosimetry) electrometer. This chamber is normally intended to be used as reference chamber during dosimetry commissioning especially for small fields. The control was performed on a Synergy Beam Modulator Accelerator (Elekta AB, Sweden). Previously, the detector response was studied in terms of repeatability, linearity and influence of the dose rate value with static beams. Then VMAT (clockwise and counter-clockwise) beams with a sliding slit with variation of the dose rate, gantry rotation speed and leaves speed were studied in terms of repeatability and constancy. The measured signal was corrected from the daily output and compared to the routine measurement done with a Farmer-type ionization chamber (FC65-P, IBA Dosimetry) placed in a 15 × 15 × 5 cm 3 Plexiglas phantom centered on the couch. Results: The first tests demonstrated the need for pre-irradiation of at least 2000 MU. A relative standard deviation of less than 0.1% was obtained for static beam repeatability and 0.4% for VMAT beams. The detector showed a dependence on the dose rate with a deviation of 1.2% for the extreme dose rate values. The study of linearity showed a good correlation (R 2  = 1). The monitoring of the constancy check of the VMAT beams with the Stealth® chamber seems to follow the same trend of variation as that obtained with the Farmer chamber. Conclusions: This study seems to show the possibility to use this detector for a constancy check of VMAT beams. In order to validate this result, a sensitivity study will be carried out by introducing errors into the VMAT beams.